2014
DOI: 10.1002/app.41697
|View full text |Cite
|
Sign up to set email alerts
|

Stress relaxation behavior of starch powder‐epoxy resin composites

Abstract: The purpose of the present study is to investigate the quasi-static and the viscoelastic behavior of epoxy resin reinforced with starch powder. An increase in the elastic modulus on the order of 42% was achieved; a behavior that was predicted by the modulus prediction model (MPM). Next, the composite was subjected to flexural relaxation experiments, in order to determine the relaxation modulus, at different filler-weight fractions and flexural deflections imposed. The viscoelastic models of the standard linear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 26 publications
(27 reference statements)
0
14
0
1
Order By: Relevance
“…Property prediction model (PPM) is a semiempirical model developed by the first author and is used to predict the property variation with filler–volume fraction. It is the improved version of the modulus prediction model (MPM), already presented in previous works , after it was found by others that it can predict more material properties in addition to the elastic modulus . The PPM model is described by the following equation: Pc=(λκ)PfVf2+κ(PfPm)Vf+Pm where P c is the current property value of the composite, P f and P m is the filler and matrix property value respectively, λ is the dispersion parameter and κ the adhesion parameter .…”
Section: Theoretical Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…Property prediction model (PPM) is a semiempirical model developed by the first author and is used to predict the property variation with filler–volume fraction. It is the improved version of the modulus prediction model (MPM), already presented in previous works , after it was found by others that it can predict more material properties in addition to the elastic modulus . The PPM model is described by the following equation: Pc=(λκ)PfVf2+κ(PfPm)Vf+Pm where P c is the current property value of the composite, P f and P m is the filler and matrix property value respectively, λ is the dispersion parameter and κ the adhesion parameter .…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…The PPM model is described by the following equation: Pc=(λκ)PfVf2+κ(PfPm)Vf+Pm where P c is the current property value of the composite, P f and P m is the filler and matrix property value respectively, λ is the dispersion parameter and κ the adhesion parameter . Finally, the filler volume fraction is denoted by V f. As it is explained in details , the model application is taking into account the fact that at low filler concentrations the composite behavior is mainly manifested by the filler–matrix adhesion and in a lesser extent by the filler dispersion, while at high filler volume fractions dispersion of the filler into the matrix is the most important parameter dictating the overall behaviour. Knowing only two experimental points, specifically one at a very low filler concentration and a second one at a high filler concentration, one can determine the parameters κ and λ .…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…The Property Prediction Model (PPM) has been developed, by the first author, aiming to predict the composite property-value variation as a function of the filler concentration (C f ) in particulate composites. The present model is the improved version of the Modulus Prediction Model (MPM) already presented in [27,28] after it was found that it can predict a series of different material properties in addition to the elastic modulus [29]. For the model application, only two experimental points are needed.…”
Section: Property Prediction Model (Ppm)mentioning
confidence: 99%
“…[21][22][23] In the present work, the RPM has been applied in order to predict the residual compressive strength of five different materials systems as a function of the additives concentration. In all cases and independently of the material system under consideration, function M was found as: M ¼ C 2 , where C is the percentage concentration of the phase added.…”
Section: The Rpm Model Presentation and Applicationmentioning
confidence: 99%
“…The RPM model has already been successfully applied to all the above-mentioned cases as well as to many others such as materials property degradation after thermal shock cycling, and strength reduction due to materials discontinuities (central hole, edge cracking, etc.). 2123…”
Section: Residual Property Modeling and Porosity Estimationsmentioning
confidence: 99%